Effect of Leaf Extract Sirih (Piper betle L.) and on Future Soaking Time Freshness of Flowers Rose (Rosa sinensis L.) - Devi Wahyuni; Rita Hayati; . Nurhayati (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Rose (Rosa sinensis L.) is one commodity florikulture important as a component in agribusiness systems and as an ornamental plant. Roses as an ornamental plant has two types, namely roses for the garden and roses for cut flowers. Cut flowers are marketed must have a good quality. One aspect of the desired quality is the life of a cut flower freshness long. Age freshness of cut flowers can be done by granting long soaking solution which is natural as a preservative. This study aims to get the right composition of the soaking solution between betel leaf extract, citric acid and sugar to prolong the freshness of roses. Results showed that betel leaf extract very significant effect on the diameter of the roses in full bloom at 2, 6, 8, and 10 DAT (Days After Treatment), 8 and 10 flower sepals DAT, the index rose florescence 8 and 10 DAT, the index kelayuan rose 6.8 and 10 DAT and organoleptic (color), real influence on organoleptic (texture) and had no significant effect on the diameter of flowers in full bloom 4 DAT, petal number 2, 4, 6, 8 and 10 DAT, sepals index flower 2, 4 and 6 DAT, and florescence index rose2, 4 and 6 DAT. The best treatment is found in the treatment of betel leaf extract 200 g / L of water. Soaking time no real effect on the diameter of roses in full bloom, the number of petals, sepals index, the index rose florescence, indexes wilted roses and organoleptic (color and texture). Soaking time is best found in the soaking time of 9 days. There is a significant interaction between treatment betel leaf extract and soaking time on indexes sepals on 10 DAT and florescence index rose at 4 DAT.